Sindiran Antiphrassis Warganet di Instagram @Mastercorbuzier : Tuduhan Pelecehan Seksual - Dewi, Tessa Yuliana; Inayatillah, Fafi (Universitas Tidar, 2023)
The increasing use of social media on Instagram has triggered the emergence of sarcastic comments, particularly concerning the topic of sexual harassment, in the comment section. This research aims to identify the types and meanings of the sarcasm used by netizens on the Instagram account @mastercorbuzier, as well as the functions of these sarcastic remarks. This research follows a qualitative descriptive approach, using descriptive sentences rather than numbers. The data for this study consist of Instagram comments on the @mastercorbuzier account, which are expressed in sentence form. The data collection procedure employs the observation and note-taking method. The data are analyzed based on their meanings, types, and functions, and the results are then summarized. The data analysis technique involves an interactive model that examines the written language of sarcasm from Dedy Corbuzier's Instagram account, records the identified data, analyzes them descriptively, and draws conclusions from the research findings. The findings of this study reveal that the stylistic device of sarcasm, known as antiphrasis, appears in 24 instances. These instances demonstrate that Instagram users employ implicit language that conveys the opposite or contrary meaning to express their comments. Furthermore, out of the 23 instances, netizens predominantly utilize connotative meanings to convey their intentions in the comment section. Lastly, the most common linguistic function employed by netizens, with 13 instances, is discourse, which serves to discuss ongoing events.